Satu Suro Ceremony Tradition: Tahlilan in the Perspective of Islamic Religious Education - Isdiana Isdiana; Mustafa Abu Zaid; Saeed Akhtar (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: The aim of this research is to investigate and understand the meaning and religious context of the Satu Suro Ceremony Tradition: Tahlilan in the Perspective of Islamic Religious Education. Methodology: This research uses qualitative methods with a naturalistic design. This research data collection technique uses structured interviews and direct observation. Data analysis in this research uses the Miles and Hubermen model. Main Findings: The results of this research show that the Satu Suro Tradition, especially Tahlilan, has been proven to have a significant positive impact on society. Tahlilan is not just a religious ritual; More than that, this tradition strengthens a sense of togetherness, mutual cooperation and religious values. Active participation from various levels of society creates strong social ties, from families to the younger generation. In the context of Islamic religious education, the integration of Tahlilan helps students understand religious teachings more deeply and apply them in the context of local culture and traditions. Tahlilan is a source of inspiration and spiritual guidance, creating a deeper understanding of togetherness, solidarity and spirituality in Islam. Novelty/Originality of this study: This research presents an innovative concept in integrating local wisdom values and Islamic teachings, highlighting the close relationship between religion and culture. This novelty becomes the basis for new thinking in developing an Islamic religious education curriculum in madrasas, Islamic boarding schools or public schools that is not only relevant to the local cultural context, but also penetrates the meaning of religion in people's daily lives.